Comment on 'Molecular structure-dependent deformations in boron nitride nanostructures subject to an electrical field' - Seyyed Fakhrabadi, Mir Masoud (Journal of physics. D, Applied physics, 2016)
The nanomechanical deformation and buckling characteristics of boron nitride nanostructures including boron nitride nanotubes and sheets under an external electric field were analyzed in Zhang et al (2013 J. Phys. D: Appl. Phys. 46 235303). A mistake in the consideration of the type of chemical bond between boron and nitride atoms was made that affected the reported results. The authors considered the bond between the atoms ionic but they actually bond to each other via covalent bonds. In this comment, the mentioned problem is going to be discussed and its effects on the final results are to be analyzed.